Lettercard from Éamonn Duggan to his fiancée May Kavanagh, written from Trim, Co. Meath, - Duggan, Éamonn, 1874-1936
Duggan's undated note concerns his fundraising efforts in Co. Meath during the 1918 General Election campaign.